2014
DOI: 10.1021/ac5006475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bioaccumulation Kinetics of Gold Nanorods in Vital Mammalian Organs by Means of Total Reflection X-Ray Fluorescence Spectrometry

Abstract: This work presents the first application of total-reflection X-ray fluorescence (TXRF) spectrometry, a new and powerful alternative analytical method, to evaluation of the bioaccumulation kinetics of gold nanorods (GNRs) in various tissues upon intravenous administration in mice. The analytical parameters for developed methodology by TXRF were evaluated by means of the parallel analysis of bovine liver certified reference material samples (BCR-185R) doped with 10 μg/g gold. The average values (n = 5) achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Previous studies showed an almost immediate clearance of the GNR from the circulation after the administration. In blood serum, GNR immediately forms a protein corona, causing rapid recognition and internalization by components of the reticuloendothelial system and mainly accumulates in liver . These studies revealed that the accumulated GNRs in a healthy liver did not cause significant hepatotoxicity as evidenced by biochemical and histological measurements, even at high doses (4 µg g −1 by weight) of systemically administrated GNR.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies showed an almost immediate clearance of the GNR from the circulation after the administration. In blood serum, GNR immediately forms a protein corona, causing rapid recognition and internalization by components of the reticuloendothelial system and mainly accumulates in liver . These studies revealed that the accumulated GNRs in a healthy liver did not cause significant hepatotoxicity as evidenced by biochemical and histological measurements, even at high doses (4 µg g −1 by weight) of systemically administrated GNR.…”
Section: Resultsmentioning
confidence: 84%
“…One crucial factor that requires further study is the determation of the fate of GNRs in the host system. In most studies, GNRs were systemically administrated and subsequently distributed in organs . For the implanted cardiac construct, however, it has been speculated that the GNRs could be mainly internalized by the local cardiac cells after the degradation of biomaterial matrix and only a small amount of them may enter circulation system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological and clinical materials generally need to be pretreated to remove the organic matrix which would increase the background signal and thus worsen the detection limits. Common pretreatment methods are ashing, acid digestion, or purification using chromatographic methods [42][43][44][45][46][47][48][49][50]. Mineral oil, vegetable oil or fatty acid containing samples like creams and lotions can be diluted with a solvent or if necessary subjected to cold oxygen plasma ashing to remove excess carbon.…”
Section: Biological and Food Applicationsmentioning
confidence: 99%
“…The authors simulated and investigated experimentally the sputter yield of ZnO and GaAs nanowires, which were implanted with energetic Mn ions at room temperature. Fernandez-Ruiz et al 408 applied TXRF spectrometry to the evaluation of bioaccumulation kinetics of gold nanorods (NR) in vital mammalian organs. A clearly enhanced sputter yield for the irradiated nanowires compared with bulk was observed, which was also corroborated by simulations showing a maximum if the ion range matched the nanowire diameter.…”
Section: Thin Lms Coatings and Nanomaterialsmentioning
confidence: 99%